Sistem electronic theses postgraduate / Mariana Abdul Majid - Mariana, Abdul Majid (2001)
The technology improvement nowdays, has been supported a system development with the existence of various software forms. The competitive exists to fill up the user needs together with the development of information technology in this century. A software which will be developed is appropiate with a current development and user needs that always wishing for the innovation and also to reduce the usage of time. This research report will explain the phases of the system development, from the earlier research to the implementation process and test made. This system is call "Electronic Theses_PostGraduate". The main objective of this Electronic Theses PostGracluate development is to provide one special platform to the users (PostGraduate students, lecturers and admininstraiors), to manage a theses reports. So that it can be updated and implemented with the use or more systematic technique. The PostGraduate Electronic Theses system is a system which is improved onlinely and acts as user assistant to get or achieve the these. information of previous sessions with more efficient, easier and more effective. The more effective and efficient technique preparation in this information system managment gives a new dimension towards electronical theses managment. To improve that system, the ASP has been choosed as a programming language. Because of ASP ability can interact with the database Microsoft SQL server. so SQL(Structure Query Language) is accepted to form the database for saving the importants data in the system.